A real-world pharmacovigilance study of FDA adverse event reporting system (FAERS) events for etrasimod - Wu, Yingxiu; Ke, Wei; Li, Huibiao (Frontiers in Pharmacology, 2025)
ObjectiveTo characterize the post-marketing safety profile of etrasimod using the latest data from the FDA Adverse Event Reporting System (FAERS), and to provide a comparative analysis versus other sphingosine-1-phosphate (S1P) receptor modulators.MethodsAE reports associated with etrasimod were retrieved from FAERS (Q1 2004 – Q2 2025). Disproportionality analyses were conducted using the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS) methods. A comparative analysis against fingolimod and ozanimod was performed to contextualize findings.ResultsWe identified 2,104 AE reports from 967 patients—a larger cohort than previously described. The most frequent AEs were drug ineffectiveness, condition aggravated, headache, and dizziness. Signals were concentrated in gastrointestinal, general, and nervous system disorders. Strong signals included ulcerative proctitis, increased faecal calprotectin, and macular oedema. Critically, our comparative analysis suggested a potentially distinct safety profile for etrasimod, such as a more favorable signal for lymphocyte count decreased compared to other S1P modulators.ConclusionThis large-scale, updated analysis confirms the established safety profile of etrasimod while providing novel, comparative insights. Our findings, derived from the most recent and extensive FAERS dataset to date, underscore that etrasimod’s real-world safety is characterized by class-related AEs and disease exacerbations. The lack of unexpected signals remains reassuring. The frequent reporting of lack of efficacy highlights the need for close monitoring, and the comparative data offer valuable context for clinicians selecting S1P receptor modulator therapy.